Polygenic Effect on Tau Pathology Progression in Alzheimer's Disease. Issue 4 (4th January 2023) - Rubinski, Anna; Frerich, Simon; Malik, Rainer; Franzmeier, Nicolai; Ramirez, Alfredo; Dichgans, Martin; Ewers, Michael; ,
Abstract : Objective: Polygenic variation accounts for a substantial portion of the risk of Alzheimer's disease (AD), but its effect on the rate of fibrillar‐tau accumulation as a key driver of dementia symptoms is unclear. Methods: We combined the to‐date largest number of genetic risk variants of AD (n = 85 lead single‐nucleotide polymorphisms [SNPs]) from recent genome‐wide association studies (GWAS) to generate a polygenic score (PGS). We assessed longitudinal tau‐positron emission tomography (PET), amyloid‐PET, and cognition in 231 participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Using the PGS, together with global amyloid‐PET, we predicted the rate of tau‐PET increases in Braak‐stage regions‐of‐interest and cognitive decline. We also assessed PGS‐risk enrichment effects on the required sample size in clinical trials targeting tau pathology. Results: We found that a higher PGS was associated with higher rates of tau‐PET accumulation, in particular at elevated amyloid‐PET levels. The tau‐PET increases mediated the association between PGS and faster cognitive decline. Risk enrichment through high PGS afforded sample size savings by 34%. Interpretation: Our results demonstrate that the PGS predicts faster tau progression and thus cognitive decline, showing utility to enhance statistical power in clinical trials. ANN NEUROL 2023;93:819–829